How office design affecting employees’ productivity? A study on natural gas industry - Mohamed Abdul Kadir, Juliana; Jaini, Azila; Subramaniam, Geetha; Zulkipli, Izyan Nadirah; Bakar, Ahmad Naqiyuddin (UiTM Cawangan Johor, 2024)
In the current workplace and office design, organization recognize the importance of leveraging the work environment, both in terms of aesthetics and functionality to enhance employee productivity. The arrangement of the office space and the overall of office design which include workflow play a crucial role in employee satisfaction and makes a positive impact on the well-being of the employees. This study examines the impact of office design on employee productivity in a processed gas industry, specially considering factors such as furniture availability, environmental noise, ambient temperature, ambient lighting and space arrangement